Database-Assisted Spectrum Sharing in Satellite Communications: A Survey - Marko Hoyhtya; Aarne Mammela; Xianfu Chen; Ari Hulkkonen; Janne Janhunen; Jean-Christophe Dunat; Jonathan Gardey (IEEE Access, 2017)
This survey paper discusses the feasibility of sharing the spectrum between satellite telecommunication networks and terrestrial and other satellite networks on the basis of a comprehensive study carried out as part of the European Space Agency's Advanced Research in Telecommunications Systems programme. The main area of investigation is the use of spectrum databases to enable a controlled sharing environment. Future satellite systems can largely benefit from the ability to access spectrum bands other than the dedicated licensed spectrum band. Potential spectrum sharing scenarios are classified as: a) secondary use of the satellite spectrum by terrestrial systems, b) satellite system as a secondary user of spectrum c) extension of a terrestrial network by using the satellite network; and d) two satellite systems sharing the same spectrum. We define practical use cases for each scenario and identify suitable techniques. The proposed scenarios and use cases cover several frequency bands and satellite orbits. Out of all the scenarios reviewed, owing to the announcement of many different mega-constellation satellite networks, we focus on analyzing the feasibility of spectrum sharing between geostationary orbit (GSO) and non-geostationary orbit (NGSO) satellite systems. The performance is primarily analyzed on the basis of widely accepted recommendations of the Radiocommunications Sector of the International Telecommunications Union. Finally, future research directions are identified.